PERAN PEMERINTAH KELURAHAN DALAM PENINGKATAN KESEJAHTERAAN MASYARAKAT DI KELURAHAN MATA ALLO KECAMATAN BAJENG KABUPATEN GOWA - Muhammad Arifin; Alimuddin Said; Andi Nuraeni Aksa (Department of Government Studies Universitas Muhammadiyah Makassar, 2013)
The purpose of this study was to analyze the role of the government in Mataallo sub-district, Bajeng district, Gowa Regency, as well as the factors of social welfare improvement in Mataallo sub-district, Bajeng District, Gowa regency. Type of this research was survey study which was direct to the object of the research descriptively by the informants that had been determined in advance. The data collected primarily and secondarily by data collection techniques as follows: observation, and in-depth interviews to the informants and the last five years secondary data. The data were analyzed descriptive qualitatively. Based on the research results showed that the Government's role in improving public welfare in the Mataallo sub-district, Bajeng District, Gowa regency, from those, it can be concluded that the implementation of the government's role could be seen from the organizers of the event of sub-district government, community empowerment, community services, the implementation of public peace and order, and maintaining public service infrastructure and facilities were not maximum, it was proved by the activities and urban government programs did not run optimally, empowerment and improving the welfare of the people in the Mataallo sub-district, Bajeng district, Gowa regency. Factors affecting the public welfare in the Mataallo sub-district, Bajeng district, Gowa regency included internal factors and external factors. Internal factors were income, education, and employment, while external factor was the ease. Tujuan dilaksanakan penelitian ini adalah untuk menganalisis peran Pemerintah Kelurahan Mataallo Kecamatan Bajeng Kabupaten Gowa dan faktor-faktor dalam peningkatan kesejahteraan masyarakat di Keurahan Mataallo Kecamatan Bajeng Kabupaten Gowa. jenis penelitian adalah penelitian survey langsung ke objek penelitian dengan tipe deskriptif dengan informan yang telah di tentukan. Data dalam penelitian ini di kumpul dengan data prime dan sekunder yang menggunakan teknik pengumpulan data berupa ; observasi, dan wawancara secara mendalam terhadap informan dan data sekunder lima tahun terakhir. Data tersebut di analisis secara deskriptif kualitatif. Berdasarkan hasil penelitian mnnjukan bahwa peran Pemerintah kelurahan dalam peningkatan kesejahteraan masyarakat di Kelurahan Mataallo Kecamatan Bajeng Kabupaten Gowa, ternyata dapatlah disimpulkan bahwa pelaksanaan peran pemerintah kelurahan dilihat dari penyelenggara kegiatan pemerintah kelurahan, pemberdayaan masyarakat, pelayanan masyarakat, penyelenggaraan ketentraman dan ketertiban umum, pemeilharaan prasarana dan fasilitas pelayanan umum, belum maksimal, seperti kegiatan dan program pemerintah kelurahan tidak berjalan secara maksimal, belum maksimalnya pemberdayaan masyarakat dan peningkatan kesejahteraan masyarakat di Kelurahan Mataallo Kecamatan Bajeng Kabupaten Gowa. Faktor yang mempengaruhi peningkatan kesejahteraan masyarakat di Kelurahan Mataallo Kecamatan Bajeng Kabupaten Gowa meliputi faktor internal dan faktor eksternal. Faktor internal ; pendapatan, pendidikan, dan pekerjaan, sedangkan faktor eksternal seperti kemudahan.